Birds of Adlay and forest watershed in Surigao del Sur and notes on the diet of select species - Carig, Hadassah Faith C. (2007)
Adlay and Sipangpang Forest Watersheds are situated within Mt. Hilong-hilong range. The range is one of the identified in Mindanao-Eastern Visayas EBA supporting areas of lowland dipterocarp forests. Currently, avifauna of Mt. Hilong-hilong was incompletely known and a study was conducted to provide additional information on avifaunal richness, on bird diet and on existing threats within the area. A total of 91 bird species representing 38 families was recorded from the two sites with endemic species composing half of the total number of species in each watershed. Near threatened species M. picina, R. goodfellowi, A. primigenius, A. leucocephalus, and B. hydrocorax, vulnerable species A. luzonica, E. steeriti, F. basilanica and the endangered species G. criniger were spotted from the two watersheds. Species with the highest relative abundance in Adlay were H. philippinus (0.1387; point counts) and P. urostictus (0.2381 mistnets) while in Sipangpang species M. stiaticeps obtained highest value for point counts (0.0775) and P. urostictus from mistnets (0.2857). examined gut samples from voucher specimens revealed arthropod prey items. High endemicity and presence of threatened species highlighted the value of the watersheds as bird habitats. Existing habitat fragmentation, logging, hunting and mining underscore the urgency of conserving the currently unprotected watersheds